Acid dyeing for green solvent processing of solvent resistant semiconducting organic thin films. Issue 11 (1st September 2020) - Harding, Cayley R.; Cann, Jonathan; Laventure, Audrey; Sadeghianlemraski, Mozhgan; Abd-Ellah, Marwa; Rao, Keerthan R.; Gelfand, Benjamin Sidney; Aziz, Hany; Kaake, Loren; Risko, Chad; Welch, Gregory C.
Abstract : The alcohol and water-based processing of a perylene diimide (PDI) organic semiconductor into large area and solvent resistant films is reported. Abstract : The alcohol and water-based processing of a perylene diimide (PDI) organic semiconductor into large area and solvent resistant films is reported. The compound, PDIN-H, is an N-annulated PDI dye with a pyrrolic NH functional group that can be deprotonated to render the material soluble in polar solvents. Addition of NaOH to mixtures of PDIN-H in 1-propanol results in a progressive color change from orange/red to purple with increasing equivalents of base. Use of 1 molar equivalent of NaOH was found to fully dissolve the PDIN-H in alcohol solvents up to a concentration of 10 mg mL −1 . Primary alcohols 1-propanol to 1-hexanol as well as 2-propanol were used. All solutions were readily spin-coated or slot-die coated into uniform thin films. Solutions in 1-propanol could be coated with concentrations up to 50 mg mL −1 . All films were red in color and characterized by optical absorption spectroscopy confirming the existence of the parent PDIN-H species in the film. Single crystal X-ray diffraction was used to determine the molecular packing of PDIN-H. Films showed no signs of dewetting, swelling, or dissolution upon exposure to 2-propanol, water, or o -xylene via coating or dipping indicating they were solvent resistant. To exploit the semiconducting properties of these PDIN-H films, organic photovoltaic devices were fabricated using the films as electron transport layers in inverted type P3HT:PC61 BM bulk heterojunction devices. Moreover, the PDIN-H films changed from red to purple upon exposure to butylamine vapors which prompted the investigation of hydroxide free processing. Indeed, films of PDIN-H were easily formed by processing with 1-propanol/butylamine or water/butylamine solutions.